Penataan Permukiman Lingkungan Masjid Al-Muttqin Sebagai Wisata Religi di Kaliwungu - Arzaq, Miftahul; , Ir. Nurhasan, MT (2016)
Background of the planning and design of settlements neighborhood of Al-Muttaqin Kaliwungu is based on a problems that often occur in areas Kaliwungu especially in the neighborhood around the mosque Al-Muttaqin Kaliwungu. The main problems that occur in Kaliwungu is the lack of attention from the public to protect the environment, so that many potential covered by untidiness made citizens. Kaliwungu has a lot of potential, among others, is the number of boarding schools and the tomb guardian. With boarding schools and tomb guardian Kaliwungu frequented by the public both of the families of students who studied at boarding school in Kaliwugnu or for pilgrimage at the tomb tomb guardian. The daily life of citizens is quite religious Kaliwungu add a thick Kaliwungu name as the city of students. Over time his runs into the identity of religious life Kaliwungu residents began to fade, not only was the state of the city also increased chaotic and looks shabby because it is not organized. From that basic idea of planning and environmental settlements masjid al-Muttaqin Kaliwungu as religious tourism Issues raised from the translation above is how the process approach consistent with the development of the area neighborhood settlements masjid al-Muttaqin as religious tourism in Kaliwungu. With the settlements the mosque al-Muttaqin expected to foster a sense of maintaining, managing, and taking care of the city. It is also to menagangkat back Kaliwungu religious identity of citizens. It is expected that religious tourism in the city could become an icon Kaliwungu Kaliwungu